Pengaruh Bioremediasi Tanaman Eceng Gondok (Eichornia crassipes) Terhadap Penurunan Amoniak, pH, Minyak dan Lemak pada Limbah Minyak Mentah Wonocolo Bojonegoro - Ari Bahtiar, Lukman; Wasiq Hidayat, Jafron (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
This study aims to determine how much water hyacinth absorbs pollution, effectiveness and howsignificant the difference in pollution in crude oil waste after and before planting waterhyacinth. The sample tested in this oil waste is NH3, pH of oil and fat. The research design usedwas a randomized block design (RBD) of 5x1 with 3 replications with variations in theconcentration of crude oil waste consisting of 5 dilution treatments, namely: P0 (100%), P1(75%), P2 (50%), P3 (25%) and P4 (0%) and observed for 21 days. Data from the researchresults were analyzed using Microsoft Excel software to test the value of efficiency. The resultsof the study after phytoremediation of water hyacinth were able to reduce NH3 content, pH ofoil and fat. Water hyacinth can absorb contamination caused by crude oil waste effectively. It isproven that during the phytoremediation process NH3 content in crude oil waste decreasesbelow the water quality standard, in oil and fat parameters it can fall below the water qualitystandard except treatment P4. Water hyacinth can reduce NH3, pH Oil and fat in crude oilwaste are significant.